Main Assessment Factors of Academic Quality for Graduate Programs: A Comparative Analysis - Soto-Grant, Andrea; Castro-Garro, Karla (Revista Electrónica Educare, 2024)
Objective. This article derives from a research study that aims to identify the primary factors in assessing the academic quality of postgraduate programs, as applied by various self-assessment models in the Ibero-American region. Methodology. A qualitative investigation was conducted using comparative education methods to analyze seven existing self-assessment models in Chile, Ecuador, Central America, Colombia, and Spain. Units of analysis were established to compare the criteria and evidence of each model, utilizing individual and unified matrices to systematize all studied elements. Results. The findings identified levels of relevance between the factors and their corresponding evidence in determining the quality of a graduate program. Conclusion. Among all the proposed categories for analysis, the three most important are pedagogical factors, administrative factors, and impact assessment.